Sintesis Periodesasi Jonathan A. C. Brown dan Muhammad Abdul Rauf: Perkembangan Literatur Hadis dari Masa Sahifah hingga Fase Analitis - Ilham Syamsul (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2026)
This article aims to examine the development of hadith literature from the sahifah period to the analytical phase by tracing the dynamics of transmission, codification, and canonization of hadith in the Islamic scholarly tradition. This study focuses on analyzing the thought patterns of Ahlu Al-Ra'y and Ahlu Al-Hadis and formulating a periodization of the development of hadith literature through a synthesis of the thoughts of Jonathan A.C. Brown and Muhammad Abdul Rauf. This research uses a qualitative method based on literature review with a descriptive-analytical approach. The results of this study are the synthesis of Brown and Abdul Rauf's periodizations showing that the development of hadith literature took place through several main phases, namely the sahifah, musannaf, musnad, sahih, sunan, canonization, and the analytical phase. Each phase reflects the response of scholars to the social, political, and intellectual challenges of their time. The methodological differences between Ahlu Al-Ra'y who emphasize rationality and Ahlu Al-Hadis who prioritize the transmission of narrations helped shape the system of hadith criticism and verification. Brown and Abdul Rauf's synthesis of periodization shows that the development of hadith was not linear, but rather influenced by the interaction between oral and written traditions, and the normative needs of the community